Quality improvement in plastic injection moulding products by using lean sigma tools - Chaw, Sok Hui, 1988-; Wan Harun Wan Hamid, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2011